2017
DOI: 10.3329/bjch.v39i2.31538
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Supplementation and Its Effect on Weight and Feed tolerance in Preterm Low Birth Weight Newborns: A Clinical Trial

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 19 publications
(23 reference statements)
1
9
0
Order By: Relevance
“…However, in our study we compared birth weight (P = 0.083) and weight at discharge (P = 0.196), that shows there were no significant differences in weight variation (P = 0.437) in each group. One other study also demonstrated similar results, that weight gain was not affected by probiotic supplementation (24). However results of a similar studies in preterm infants born at less than 34 weeks showed that the mean weight gain of newborns in probiotic group was significantly higher than control group (14,25).…”
Section: Discussionmentioning
confidence: 57%
“…However, in our study we compared birth weight (P = 0.083) and weight at discharge (P = 0.196), that shows there were no significant differences in weight variation (P = 0.437) in each group. One other study also demonstrated similar results, that weight gain was not affected by probiotic supplementation (24). However results of a similar studies in preterm infants born at less than 34 weeks showed that the mean weight gain of newborns in probiotic group was significantly higher than control group (14,25).…”
Section: Discussionmentioning
confidence: 57%
“…0.72 ± 0.04 cm/week; p = 0.67, Linear growth b : 0.89 ± 0.04 vs . 0.87 ± 0.04 cm/week; p = 0.17 Choudhury et al [ 43 ] 2015 Single centre Bangladesh GA b : 31.9 ± 1.32 vs . 32.04 ± 1.26; p = 0.76, BW: 1000 - <1800. p = NS n = 28/30 vs. 29/35; TS6 Probiotic (Eight viable strains mixture of Lactobacillus and Bifidobacterium (20 billion/2 gram) vs .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-two RCTs were single centre [ 35 , 36 , 39 , 40 , 42 , 43 , 45 , 46 , 48 , 49 , 51 , 53 58 , 60 64 , 67 , 68 ], while eight were multicentre RCTs [ 34 , 37 , 38 , 41 , 44 , 47 , 50 , 52 , 59 , 65 , 66 ]. Primary and secondary outcomes in the included studies varied (Supplementary Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations